Análisis de la tipificación de la corrupción privada en el Perú: ¿Una estrategia global contra la corrupción también debe involucrar a los particulares? ¿Y a las empresas? - Madrid Valerio, Cecilia (2019)
In this article the authors analyze the background of the crimes of corruption in the private sphere (section 241-A) and corruption inside private entities (section 241- B). The purpose is to determine the political-criminal need for their legal recognition and the importance of their repression as part of a global strategy against corruption that aims to hold accountable both individuals and private entities that benefit from acts of corruption commited by them, according to the rules established by Peruvian Law 30424.